Evaluation of Nematode Pests and Fungal Diseases of Ceratotheca Sesamoides in Ilorin - Izuogu, N. B; Egberongbe , O. L; Oyedunmade , E. E. A (Asian Journal of Agriculture and Rural Development, 2012)
Field and Laboratory experiments were conducted to find out the incidence of diseases caused by nematode pests and fungal pathogens associated with two cultivars (tall and short) of black sesame, Ceratotheca sesamoides (L) Endl. Two cultivars of C. sesamoides were planted at random on the field in a completely randomized block design. Rate of fungal infection significantly differed in the two varieties and the tall cultivar had higher rate of infection. The nematode genera found associated with the plant in were Meloidogyne, Pratylenchus, Helicotylenchus, Trichodorus, Hemicricomoides, and Scutellonema while fungal pathogens were Septoria, Fusarium, and Penicillium. Although not significantly different, there was appreciable difference in the nematode population of the soil at planting, one and two months after planting. The nematode counts in and around the root did not significantly differ.